Análisis del efecto aerodinámico de chorros sintéticos en perfiles aerodinámicos típicos de turbinas eólicas (2023)
In the present work, the aerodynamic design of a DU17DBD25 type wing profile, used in wind turbines, was studied through simulation with the Ansys Fluent program. Several meshing techniques were evaluated in simulations without synthetic jet, varying the angles of attack between 10° and 20° and selecting the most efficient one in terms of lift coefficient. With the best configuration, the simulation was carried out with a synthetic jet seeking to extend the separation point of the boundary layer of the rupture in the form of turbulent flow. With the insertion of the synthetic jet, a better aerodynamic efficiency of the profile could be achieved, improving by 5% in relation to the experimental data from the literature. The detailed study of different meshing techniques made it possible to guarantee this improvement.